The miR-204-3p-targeted IGFBP2 pathway is involved in xanthohumol-induced glioma cell apoptotic death. (November 2016) - Chen, Peng-Hsu; Chang, Cheng-Kuei; Shih, Chwen-Ming; Cheng, Chia-Hsiung; Lin, Cheng-Wei; Lee, Chin-Cheng; Liu, Ann-Jeng; Ho, Kuo-Hao; Chen, Ku-Chung
Abstract: Xanthohumol (XN), a prenylated chalcone extracted from hop plant Humulus lupulus L. (Cannabaceae), has potential for cancer therapy, including gliomas. Micro (mi)RNAs are small noncoding RNAs that control gene expression. Several miRNAs have been identified to participate in regulating glioma development. However, no studies have demonstrated whether miRNA is involved in XN cytotoxicity resulting in glioma cell death. This study investigated the effects of XN-mediated miRNA expression in activating apoptotic pathways in glioblastoma U87 MG cells. First, we found that XN significantly reduced cell viability and induced apoptosis via pro-caspase-3/8 cleavage and poly(ADP ribose) polymerase (PARP) degradation. We also identified that pro-caspase-9 cleavage, Bcl2 family expression changes, mitochondrial dysfunction, and intracellular ROS generation also participated in XN-induced glioma cell death. With a microarray analysis, miR-204-3p was identified as the most upregulated miRNA induced by XN cytotoxicity. The extracellular signal-regulated kinase (ERK)/c-Fos pathway was validated to participate in XN-upregulated miR-204-3p expression. With a promoter assay and ChIP analysis, we found that c-Fos dose-dependently bound to the miR-204-3p gene promoter region. Furthermore, miR-204-3p levels decreased in several glioma cell lines compared to astrocytes. Overexpression of miR-204-3p enhanced glioma cell apoptosis. IGFBP2, an upregulated regulator of glioma proliferation, was validated by a TCGA analysis as a direct target gene of miR-204-3p. XN's inhibition of the IGFBP2/AKT/Bcl2 pathway via miR-204-3p targeting played a critical role in mediating glioma cell death. These results emphasized that the XN-mediated miR-204-3p network may provide novel therapeutic strategies for future glioblastoma therapy and drug development. Highlights: Xanthohumol enhanced 28 microRNA expressions and downregulated 3 microRNA levels in inducing glioblastoma apoptotic death. The miR-204-3p levels is the most significantly upregulated microRNA in xanthohumol-treated glioma cells. Xanthohumol upregulated miR-204-3p levels via ERK/c-Fos pathway. IGFBP2 was validated as a direct target gene of miR-204-3p. The miR-204-3p-targeted IGFBP2/AKT/Bcl2 pathway is involved in xanthohumol cytotoxicity.